Consideration concerning the granulometric composition of the northeastern soil of Brazil - Oliveira, Luiz Bezerra de (Pesquisa Agropecuaria Brasileira, 2014)
This paper points out the distribution and textural nature of a large part of the Northeastern soils of Brazil. It presents the result of the analyses of 1,796 soil samples of which 710 are from the Humid Region (Pernambuco and Alagoas States) and 1,086 from the Semi-and Region (Pernambuco and Ceará States). Graphs and tables show the distribution and percentage occurrence of the soil samples based on the textural Classification Triangle and on values of silt and clay in 10% intervals. The data indicate that 85% of the total soil samples have a percentage of silt lower than 20 and that none present silt values higher than 50%. Concerning the clay fraction, the data show that 27% of the samples appear in the zone between 0-20%, and that there are none with values higher than 80%. The incidence of the soil samples in the textural classes sand, loam sandy and sandy loam is higher in the Semi-arid Region, while the sandy clay and clay classes all more predominant in the Humid Region. There are no soil samples in the classes silt loam and silt and only a few in the classes loam, clay loam and silty clay. A comparative study between present results and data from the papers: "Levantamento de Reconhecimento dos Solos dos Estados do Rio de Janeiro e Distrito Federal (today State' of Guanabara)" (Serv. Nac. Pesq. Agronômicas 1958) and "Levantamento de Reconhecimento dos Solos do Estado de São Paulo" (Serv. Nac. Pesq. Agronômicas 1960) shows that, the granulometric composition of the soils from these States is similar to that of Pernambuco and Alagoas States (Humid Region). Also the occurrence of soil samples with silt values lower than 10% is 64% as compared with 60% for the State of Pernambuco and Alagoas. The 0-20% silt values amount to 95% for the State of Rio and São Paulo and 88% for the Northeastern Region.